TRACING THE EVOLUTION OF HISTORICAL INQUIRY: THE HISTORY OF HISTORY - Dr Khalid Bashir; Ishfaq Ahmad Mir; TN,Dr. Mohammad Iqbal Darzi; Dr.Irshad Ahmad Lone Sr.; MominSajadKar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The subject of history, as we know it today, has a long and complex history of its own. This research paper explores the evolution of the subject of history, tracing its origins to ancient civilizations and following its development through the Middle Ages, the Renaissance, the Enlightenment, and into the modern era. Through this exploration, we see how the purpose, methods, and interpretation of history have shifted and evolved, as well as the cultural, social, and political factors that have influenced its trajectory. Ultimately, this paper aims to provide a comprehensive understanding of the history of history, revealing the dynamic nature of the subject and how it has been shaped by the societies and individuals who have studied it.